2015
DOI: 10.1590/s1806-92902015000800001
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of crude protein and lipid from biofloc meals produced in an activated sludge system for white shrimp, Litopenaeus vannamei

Abstract: -The present study compared the bioavailability of crude protein and lipid from biofloc meals generated with an activated sludge system using two water sources: wastewater from shrimp experimental culture (BFL-W) and, artificially, using clean seawater (BFL-C). The sludge system operated by chemical and organic fertilization three times per week. Sampling of bioflocs occurred every two days during 81 days. To evaluate digestibility, each type of biofloc meal was incorporated into a reference diet (REF) at 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…Although the levels of ash and crude protein in the bioflocs produced in the activated sludge system were different from those reported in other studies and incompatible with the requirements of L. vannamei, Sabry-Neto, Santaella and Nunes (2015) observed that shrimp gained body mass when provided with feeds containing 30% biofloc, which was produced in an activated sludge system. The production of crude protein in the system probably increases when the C:N ratio decreases.…”
Section: Bacillus 56%contrasting
confidence: 69%
See 1 more Smart Citation
“…Although the levels of ash and crude protein in the bioflocs produced in the activated sludge system were different from those reported in other studies and incompatible with the requirements of L. vannamei, Sabry-Neto, Santaella and Nunes (2015) observed that shrimp gained body mass when provided with feeds containing 30% biofloc, which was produced in an activated sludge system. The production of crude protein in the system probably increases when the C:N ratio decreases.…”
Section: Bacillus 56%contrasting
confidence: 69%
“…Sabry-Neto, Santaella and Nunes (2015) analyzed the nutritional content of biofloc formed in this system and reported that the percentage of ash (64.9%) was higher than that obtained in other studies (24.7 and 11.8% by Kuhn et al in 2009, 27.39% by Ferreira et al in 2015, and 53.95% by Fugimura et al in 2014. The high ash content found in the biofloc probably originated from salts, since the water used to feed the reactor had high salinity (31.44±4.2).…”
Section: Bacillus 56%mentioning
confidence: 64%
“…However each nutrient may have a different fluctuation and these differences did not affect the survival or apparent feed efficiency of the shrimp or their composition. This can suggest that diets and biofloc contain sufficient nutrients for shrimp performance, probably because of a growth-promoting effect, which may be associated with trace minerals or other unknown nutrients (Sabry Neto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Less reported has been the digestibility of biofloc products [109][110][111] (Table 4). Each of the biofloc products examined was produced from a different medium and system and the protein content was relatively low in each of the products (11-22%).…”
Section: Digestibilitymentioning
confidence: 99%